Adulteração de óleo diesel e determinação do tamanho de gota de emulsões - Cunha, Danyelle Alves da (2016)
Crude oil canbe defined as a complex mixture of hydrocarbons and compounds containing S, O, N, and metals in its composition. During the production process occurs the formation of water in oil emulsions (W / O) or oil in water (O / W). These types of emulsions are harmful since they increase viscosity, reduce drainage rate and can promote the precipitation of paraffin crystals and asphaltene aggregates. Precipitation of these compounds interferes the production lines, since they are deposited in the tubing, decreasing its inner diameter and increasing production costs. The industry requires oil free of water to reduce the risks of corrosion and, consequently, reduced manufacturing costs. Therefore, the monitoring of such systems by determining the droplet size distribution (DTG) is indispensable. From the refining of crude oil, are obtained derived petroleum products such as LPG (cooking gas), kerosene, gasoline, diesel oil, among others. The diesel oil is a middle distillate, since the boiling point varies between 125ºC and 328ºC. This distillate has utmost importance as a fuel in the Brazilian road transport, leading the ranking of fuel consumption in the road sector in Brazil. Thus, the adulteration of this fuel is crescent and areadded, to this oil, products such as kerosene, biodiesel and residual oils, since they have good miscibility. Among the most widely used techniques for the study of this oil there is the infrared spectroscopy, mass spectrometry and nuclear magnetic resonance (NMR) High resolution. However, studies involving diesel adulteration by Low field -NMR hadnot been publishedyet. This study aims to verify by low field-NMR adulteration of diesel and also to determine the droplet size of emulsions water / diesel and water / biodiesel